7x+10=92(3x-4)

Simple and best practice solution for 7x+10=92(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+10=92(3x-4) equation:


Simplifying
7x + 10 = 92(3x + -4)

Reorder the terms:
10 + 7x = 92(3x + -4)

Reorder the terms:
10 + 7x = 92(-4 + 3x)
10 + 7x = (-4 * 92 + 3x * 92)
10 + 7x = (-368 + 276x)

Solving
10 + 7x = -368 + 276x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-276x' to each side of the equation.
10 + 7x + -276x = -368 + 276x + -276x

Combine like terms: 7x + -276x = -269x
10 + -269x = -368 + 276x + -276x

Combine like terms: 276x + -276x = 0
10 + -269x = -368 + 0
10 + -269x = -368

Add '-10' to each side of the equation.
10 + -10 + -269x = -368 + -10

Combine like terms: 10 + -10 = 0
0 + -269x = -368 + -10
-269x = -368 + -10

Combine like terms: -368 + -10 = -378
-269x = -378

Divide each side by '-269'.
x = 1.405204461

Simplifying
x = 1.405204461

See similar equations:

| x^2-15=85 | | -10-(-15)/5 | | 20+-3+-3=14 | | 6v-21=-3(1-5v) | | 7z+8= | | 180+92(5)=x | | 8-10/3w | | (1/2)|6-4^2| | | y=12x+2400 | | 13-6r=-6(r+1) | | 29x-7x=233 | | 16-1/2*0 | | (8r+6)+(4r-1)=14 | | 22=80n | | -7(6+3n)=2(1-5n) | | 14/2=2 | | 9r+5s+4= | | 1/9z^-3 | | (4a-3b-3)+(3a+b+5)+(7a-4b+2)= | | 92=3x-4(7x+10) | | 9-49x^2=0 | | 0=3x^2+x+4 | | -(3+5x)+2x=-6(x-7) | | 3(q-2)+2=5a-7-2q | | 29x-x=233 | | 1.10x+2.50x=1200 | | 21-8x-4+9x= | | -(-4k-4)=-k-1 | | 7(8n-1)=-7+n | | 5x-7-(3x+1)=28 | | 4x+5=7x-25 | | .50x-.05=-0.2x+.75 |

Equations solver categories